2021
DOI: 10.48550/arxiv.2105.02188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rethinking Ultrasound Augmentation: A Physics-Inspired Approach

Abstract: Medical Ultrasound (US), despite its wide use, is characterized by artefacts and operator dependency. Those attributes hinder the gathering and utilization of US datasets for the training of Deep Neural Networks used for Computer-Assisted Intervention Systems. Data augmentation is commonly used to enhance model generalization and performance. However, common data augmentation techniques, such as affine transformations do not align with the physics of US and, when used carelessly can lead to unrealistic US imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sezer et al [ 14 ] showed success with using optimized Bayesian non-local means (OBNLM) [ 15 ] to reduce speckle noise as a data augmentation technique by creating one other set of denoised data. Tirindelli et al [ 16 ] went the opposite route and looked at adding realistic artifacts and noise-reflecting deformations, reverberations, and signal-to-noise-ratio to linear ultrasound images, but did not show significant improvement in image classification. SpeckleGAN [ 17 ] also looks to add speckle noise artifacts as a data augmentation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Sezer et al [ 14 ] showed success with using optimized Bayesian non-local means (OBNLM) [ 15 ] to reduce speckle noise as a data augmentation technique by creating one other set of denoised data. Tirindelli et al [ 16 ] went the opposite route and looked at adding realistic artifacts and noise-reflecting deformations, reverberations, and signal-to-noise-ratio to linear ultrasound images, but did not show significant improvement in image classification. SpeckleGAN [ 17 ] also looks to add speckle noise artifacts as a data augmentation technique.…”
Section: Introductionmentioning
confidence: 99%